2019
DOI: 10.3390/su11236641
|View full text |Cite
|
Sign up to set email alerts
|

Interrelation between Eco-Innovation and Intra-Industry Trade—A Proposal for a Proxy Indicator of Sustainability in the EU Countries

Abstract: The “innovation–trade” interrelation has been a subject of research for decades. Nowadays, in the context of the growing importance of sustainable development, the role of eco-innovation is essential for promoting a rapid economic growth in each country. In this sense, eco-innovation influences the level of intra-industry trade stimulating international trade to adopt environmentally-friendly technologies. In general, the evaluation of eco-innovation in EU countries is done through indicators of their degree o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Moreover, vertical IIT occurs due to a variety of factor endowments, and there is a tendency that trade usually takes place between a developing country and a developed country, as is similar to the north-south trade model. Furthermore, recent research on IIT shows a tendency of inducing eco-innovations (Gallucci et al 2019) and also draws Foreign Direct Investment (FDI) inflow to countries that are more vertically integrated in IIT (Ambroziak 2016). The difference in this study is in the focus of e-commerce data to extract intra-industry characteristics of its trade in Korea, which is active in the global trade of digital goods.…”
Section: Theoretical Background Of Analysis Of Trade Structure and Li...mentioning
confidence: 97%
“…Moreover, vertical IIT occurs due to a variety of factor endowments, and there is a tendency that trade usually takes place between a developing country and a developed country, as is similar to the north-south trade model. Furthermore, recent research on IIT shows a tendency of inducing eco-innovations (Gallucci et al 2019) and also draws Foreign Direct Investment (FDI) inflow to countries that are more vertically integrated in IIT (Ambroziak 2016). The difference in this study is in the focus of e-commerce data to extract intra-industry characteristics of its trade in Korea, which is active in the global trade of digital goods.…”
Section: Theoretical Background Of Analysis Of Trade Structure and Li...mentioning
confidence: 97%
“…There is a set of theoretical and empirical models (e.g., Roy [13]; Leitão and Balogh [14]; Leitão [15]; Kazemzadeh et al [16]; Copeland and Taylor [31]; Gürtzgen and Rauscher [32]; Echazu and Heintzelman [33]; Gallucci et al, [34]; and Shapiro [35]) demonstrating that IIT, and exports quality and trade intensity improve the quality of the air and environment.…”
Section: The Relationship Between Iit and Air Pollutionmentioning
confidence: 99%
“…It is observed that intra-bloc IIT is conducive for lowering emissions and consequently the adverse effects of climate change (Leitão & Balogh, 2020). Acknowledging the role of institutional factors, Gallucci et al (2019) observed that IIT-type trade of EU member countries is influenced by their eco-innovation index scores. The cross-country analysis of Cole and Elliott (2003) noted that rising IIT is associated with declining environmental regulation differences.…”
Section: Literature Reviewmentioning
confidence: 99%
“…IIT in the presence of greater difference in technology plane (K/L ratio) and income levels, on the other hand, indicate the divergence in technology embodied in exports, in turn, underlining the existence of VIIT-type trade (Bojnec & Fertő, 2016). The stringency of environmental management policies influences the production process, and types of manufactured items produced, emission patterns, compliance cost etc., and in turn, bilateral trade flows (Gallucci et al, 2019; Gürtzgen & Rauscher, 2000). The environmental policy variable was proposed by Cole and Elliott (2003) to analyze how the difference in the environmental regulations influence trade in general and IIT-type trade in particular.…”
Section: Data and Empirical Modelmentioning
confidence: 99%